Nonlinear Optical Fibers, Their Properties, and Applications - Ghimire, B. R. (Journal of Nepal Physical Society, 2020)
Nonlinear optical properties and preparation of nonlinear optical fiber based on Bismuth oxide were described. Wavelength dependence of refractive index of ABH160 and B027 was studied and analyzed. Working and construction of optical ON-OFF switches, based on Bi-HNLF was reported. It was investigated that refractive index of ABH160 and Bo27 were found to be exponentially decaying as a function of wavelength. Absorption coefficient of ABH160 as a function of wavelength was found to be decaying exponentially. In optical fiber the total group velocity dispersion is divided into the material dispersion DM and waveguide dispersion DW. Material dispersion and waveguide dispersion were calculated theoretically and a good agreement with the experimental result. The process of four wave mixing and consequences was reviewed.